How to restore rotation center in total hip arthroplasty for developmental dysplasia of the hip by recognizing the pathomorphology of acetabulum and Harris fossa? - Heng Zhang; Jiansheng Zhou; Jianzhong Guan; Hai Ding; Zhiyan Wang; Qirong Dong (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Purpose To restore rotation center exactly in total hip arthroplasty (THA) is technically challenging for patients with end-stage osteoarthritis due to developmental dysplasia of the hip (DDH). The technical difficulty is attributable to the complex acetabular changes. In this study, we investigated the pathomorphology of acetabulum and Harris fossa of Crowe types I to IV and discussed the method of restoring rotation center of the hip. Methods This study retrospectively reviewed 56 patients (59 hips) who underwent cementless THA due to end-stage osteoarthritis of DDH. The pathomorphology of acetabulum and Harris fossa was observed during operations. Using the preoperative and postoperative pelvic radiographs, the vertical and the horizontal distances of hip rotation center were measured in order to evaluate the effects of restoring rotation center of the hip. Results Adult DDH acetabulum could be classified into four basic pathological types which include the shallow cup shape, the dish shape, the shell shape, and the triangular shape. Adult DDH Harris fossa could be classified into four pathological types, including the crack shape, the closed shape, the triangle shape, and the shallow shape, in accordance with the osteophyte coverage. The vertical and horizontal distances of hip rotation center on the pelvic radiographs before and after operations were as follows: the preoperative vertical distance of hip rotation center was (39.96 ± 5.65) mm, and the postoperative one was (13.83 ± 2.66) mm; the preoperative horizontal distance of hip rotation center was (42.15 ± 6.42) mm, and the postoperative one was (28.12 ± 4.56) mm. Conclusions The acetabulum and Harris fossa can display different pathological types on account of different degrees of dislocation and osteophyte hyperplasia in the end-stage osteoarthritis of adult DDH. The hip rotation center can be accurately restored by locating the acetabular center with Harris fossa and acetabular notch as the marks.